The materiality of death, the supernatural and the role of women in Late Antique and Byzantine times - Vionis, Athanasios K. (Journal of Greek Archaeology, 2019)
Although the association between women, funerary ritual and ‘magic’ in a burial context may initially seem atypical, it should be acknowledged that women have been related to birth and death throughout history. Due to their biological role in giving birth to a new human life, they may also ‘be expected to play a symmetrical role at the end of life’. Different practices related to funerary ritual and the commemoration of the dead, to the use and deposition of ritual artefacts and accompanying materials, are altogether aspects connected to a large extent with women and the domestic sphere. It has to be noted, however, that notions such as ‘religion’, ‘funerary cult’ and ‘magic’ are not always clear-cut, especially throughout Late Antiquity – Early Byzantine era (late 4th–early 8th centuries AD), when religious syncretism, or the accommodation of polytheistic traditions in Christian ideology, was common sense and a subconscious aspect of everyday life.